Library online database system for undergraduate students - Nor Athira Azlan (Kulliyyah of Information Communication and Technology, International Islamic University Malaysia, 2017)
The demand of the good quality of research especially in academic field rose the emerging of library online databases services. Internet is the network of physical objects that enable the library online database services available. Most of the universities in Malaysia have subscribed the library online databases to provide students more opportunity to explore research resources not limited only in a certain region and country but throughout the world. The services are expected to give benefit to the postgraduate and undergraduate students for academic purposes. However, most of undergraduate students are not aware of the existence of library online databases services that universities provided. They also discouraged to use the services due to the difficulties they faced when they used the services. The purpose of this research is to explore factors contribute to the uses of online databases by undergraduate students; discover the best online database features that attract undergraduate students' interest and design library online database system that suit with undergraduates' information searching preferences. Interviews and survey have been conducted at International Islamic University Malaysia, IIUM. There were 107 participants involved. As a result, current issues and problems were identified, the best library online database system features were discovered and IIUM Library Online Database System that suit with undergraduates' students information searching preferences was develop for students use.